Direct allylation of in situ generated aldehyde acyl anions by synergistic NHC and palladium catalysis - Ahire, Milind M.; Mhaske, Santosh B. (Angewandte Chemie-International Edition, 2014)
The direct regioselective allylation of in situ generated aldehyde acyl anions has been achieved by synergistic NHC and Pd catalysis. It provides an efficient access to valuable beta,gamma-unsaturated ketones under mild reaction conditions starting from easily accessible allylic carbonates and aldehydes without any preactivation. The synergistic catalysis method demonstrated herein adds a new dimension to the area of metal-mediated C allylation.
Keywords: aldehyde umpolung; C allylation; N-heterocyclic carbenes; Palladium; synergistic catalysis